2005
DOI: 10.1111/j.1742-4658.2005.04720.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and experimental analyses of inorganic phosphate transporter PiT family reveals two related signature sequences harboring highly conserved aspartic acids critical for sodium‐dependent phosphate transport function of human PiT2

Abstract: The mammalian members of the inorganic phosphate (P i ) transporter (PiT) family, the type III sodium-dependent phosphate (NaP i ) transporters PiT1 and PiT2, have been assigned housekeeping P i transport functions and are suggested to be involved in chondroblastic and osteoblastic mineralization and ectopic calcification. The PiT family members are conserved throughout all kingdoms and use either sodium (Na + ) or proton (H + ) gradients to transport P i . Sequence logo analyses revealed that independent of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 74 publications
3
57
0
Order By: Relevance
“…This signature sequence is highlighted with red letters in Figure 1A. The human proteins from this family are thought to be involved in housekeeping functions and are called PiT1 and PiT2, whereas the Neurospora crassa and Saccharomyces cerevisiae members are called Pho-4 and Pho89, respectively [32,33]. Mutations in the signature sequence of the PiT2 protein block Pi transport [34].…”
Section: Pita and Pitb-the Low-affinity Pi Importersmentioning
confidence: 99%
See 1 more Smart Citation
“…This signature sequence is highlighted with red letters in Figure 1A. The human proteins from this family are thought to be involved in housekeeping functions and are called PiT1 and PiT2, whereas the Neurospora crassa and Saccharomyces cerevisiae members are called Pho-4 and Pho89, respectively [32,33]. Mutations in the signature sequence of the PiT2 protein block Pi transport [34].…”
Section: Pita and Pitb-the Low-affinity Pi Importersmentioning
confidence: 99%
“…Mutations in the signature sequence of the PiT2 protein block Pi transport [34]. In addition to their role in Pi transport, the PiT1 and PiT2 proteins are also receptors for the gamma-retroviruses [32]. This protein family includes both Na + -dependent and H + -dependent Pi symporters.…”
Section: Pita and Pitb-the Low-affinity Pi Importersmentioning
confidence: 99%
“…Nevertheless, the analyses of a P i transport knockout PiT2 mutant protein, PiT2 E 55 Q E 91 Q E 575 Q, did provide knowledge on the mechanism of the Na ϩ transport, showing that it can occur even though the P i uptake function is abolished. The glutamates in human PiT2 positions 55, 91, and 575 are believed to locate to transmembrane domains (4,9,14,32). A former study (5) revealed that E 91 is dispensable, whereas E 55 and E 575 are critical for P i transport of PiT2.…”
Section: Hpomentioning
confidence: 99%
“…Hydropathy profiles show that the PiT paralogs are polytopic proteins and predict 10 -12 transmembrane domains (4,9,14,32) and a large hydrophilic domain near the center of each protein that has been experimentally assigned to the cytoplasmic space in PiT2 (6).…”
mentioning
confidence: 99%
“…To this aim, we constructed hPiT1 and hPiT2 chimeric proteins expressing the eYFP acceptor or Rluc donor. Since structure-function studies have excluded a role of the large intracellular loop (iLoop) in Pi transport and retrovirus binding (59)(60)(61)(62), and showed no overlapping between iLoop and the highly hydrophobic domain (57), we substituted the iLoop with eYFP and Rluc sequences ( Figure 3C). When expressed in HEK293T, the chimeric hPiT1-eYFP or -Rluc and hPiT2-eYFP or -Rluc proteins could be visualized at the plasma membrane, as shown by confocal microscopy ( Figure 3D), enabling to study their role in detecting the variation of extracellular Pi levels.…”
Section: Pit1 and Pit2 Form Hetero-oligomers Upon Variation Of Extracmentioning
confidence: 99%